2015
DOI: 10.1161/circinterventions.115.001683
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of High Platelet Reactivity in Chronic Kidney Disease

Abstract: A dverse cardiovascular events, including cardiac death and stent thrombosis, are markedly increased among those with versus without chronic kidney disease (CKD) after percutaneous coronary intervention (PCI).1-3 Residual atherothrombotic risk remains excessive among such patients even when treated with contemporary pharmacotherapy or novel stent platforms, including second-generation drug-eluting stents (DES). 4,5 Despite the strong epidemiological links between renal impairment and thrombotic risk, underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The recently published post hoc analysis of the ADAPT‐DES trial found a significantly higher prevalence of high platelet reactivity in CKD patients who were treated with clopidogrel 32. The higher prevalence of high platelet reactivity in the CKD population might be another potential explanation for the higher incidence of nonfatal target vessel MI in the CR group than in the IR group among CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published post hoc analysis of the ADAPT‐DES trial found a significantly higher prevalence of high platelet reactivity in CKD patients who were treated with clopidogrel 32. The higher prevalence of high platelet reactivity in the CKD population might be another potential explanation for the higher incidence of nonfatal target vessel MI in the CR group than in the IR group among CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Previous studies have shown that patients with CKD exhibited significantly higher platelet activation and on-treatment residual ADP-inducible platelet reactivity than patients without renal insufficiency. 20,[22][23][24] Moreover, a low response to clopidogrel might be an independent predictor of the poorer outcomes in these CKD patients. Nowadays, the use of higher than usual clopidogrel doses (600 mg as loading dose and 150 mg as maintenance dose), 25 longer therapy duration (beyond 12 months), 26 or alternative more potent thienopyridine agents such as prasugrel 27,28 or ticagrelor 29 have been proposed as ways to overcome the clopidogrel resistance in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Interventions, Baber et al 15 elegantly report the results of a post hoc analysis of the Assessment of Dual AntiPlatelet Therapy with Drug-Eluting Stents (ADAPT-DES) study, exploring the associations among CKD, HPR, and ischemic and bleeding events in a cohort of patients undergoing PCI with drug-eluting stents treated with aspirin and clopidogrel. ADAPT-DES is the largest individual registry linking platelet reactivity and clinical events reported to date 3 ; for this analysis, only patients with valid platelet function and creatinine values were included (n=8410).…”
Section: See Article By Baber Et Almentioning
confidence: 99%
“…HPR was defined as P2Y12 reaction units >208, according to consensus definition. 15 CKD was defined as creatinine clearance (CrCl) <60 mL/min, assessed using the Cockcroft-Gault formula, and patients were stratified into 3 groups: CrCl <30 mL/min (n=119), 30 to 60 mL/min (n=1248), and ≥60 mL/min (n=7043). However, because of the small number of patients with CrCl <30 mL/min, ischemic and bleeding events were analyzed comparing patients with or without CKD.…”
Section: See Article By Baber Et Almentioning
confidence: 99%
See 1 more Smart Citation